Pengaruh Apatisme Politik terhadap Kualitas Pemerintahan : Studi Kuantitatif pada Masyarakat Kota Tangerang - Fahrizal, Farhan; Setiawan, Selamet; Putra, Rizal Darma (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2026)
This study attempts to understand whether political apathy influences the quality of governance in Tangerang City using a quantitative approach. The analysis was conducted using the PLS-SEM method through the SmartPLS application. From a total population of approximately 1,965,000 residents, this study recruited 100 respondents selected through stratified random sampling from 13 sub-districts. Data were collected using a questionnaire with a five-point Likert scale that measures two main aspects: political apathy and governance quality. The test results indicate that the instrument used is quite good. Its validity and reliability values ??meet the standards, meaning that the questions in the questionnaire are indeed able to measure what should be measured, and the results are also consistent. The R-square value of 0.430 indicates that political apathy can explain approximately 43% of the variation in governance quality, while the remainder is influenced by other factors outside this study. The main result found that political apathy has a positive and significant influence on governance quality. This is evident from the path coefficient value of 0.656, with a t-statistic of 8.869 and a p-value of 0.000. This means that the relationship is statistically quite strong and reliable. Interestingly, these results indicate that the higher the level of political apathy among citizens, the higher their assessment of the quality of government. Simply put, this study concludes that political apathy is not always negative. Under certain circumstances, an attitude of "not really caring" about politics may reflect that citizens perceive the government as functioning well, thus disregarding the need for overly involved participation. This finding could serve as a reflection that the relationship between society and politics is not always clear-cut and needs to be viewed from a more flexible perspective.